Cross-sectional assessment of determinants of STIs among men who have sex with men and transgender women in Kigali, Rwanda. (6th May 2021) - Twahirwa Rwema, Jean Olivier; Herbst, Sara; Hamill, Matthew M; Liestman, Benjamin; Nyombayire, Julien; Lyons, Carrie E; Mugwaneza, Placidie; Makuza, Jean Damascène; Sullivan, Patrick Sean; Allen, Susan; Karita, Etienne; Baral, Stefan
Abstract : Background: STIs among men who have sex with men (MSM) and transgender women (TGW) continue to increase. In Rwanda, STI management relies on syndromic management with limited empirical data characterising the burden of specific STIs among MSM/TGW. This study evaluated the prevalence of syphilis, Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) and associated factors among MSM/TGW in Kigali. Methods: From March to August 2018, 737 MSM/TGW >18 years were enrolled using respondent-driven sampling (RDS). Structured interviews and HIV/STI screening were conducted. Syphilis was screened with rapid plasma reagin confirmed by Treponema pallidum hemagglutination assay. CT/NG were tested by Cepheid GeneXpert. RDS-adjusted multivariable Poisson regression models with robust variance estimation were used to evaluate factors associated with any STI, and determinants of urethral and rectal STIs separately. Results: Prevalence of any STI was 20% (RDS adjusted: 16.7% (95% CI: 13.2% to 20.2%)). Syphilis was 5.7% (RDS adjusted: 6.8% (95% CI: 4.3% to 9.4%)). CT was 9.1% (RDS adjusted: 6.1% (95% CI: 3.9% to 8.4%)) and NG was 8.8% (RDS adjusted: 7.1% (95% CI: 4.9% to 9.2%)). STIs were more common among older MSM and those with HIV (p<0.05). Of CT infections, 67% were urethral, 27% rectal and 6% were dual site. For NG infections, 52% were rectal, 29% urethral and 19% were dual site. Overall, 25.8% (23 of 89) of those with confirmed STI and returned for their results were symptomatic at time of testing. STI symptoms in the previous year (adjusted prevalence ratio (aPR): 1.94 (95% CI: 1.26 to 2.98)) were positively associated with any STI. Being circumcised was negatively associated with any STI (aPR: 0.47 (95% CI: 0.31 to 0.73)). HIV was positively associated with rectal STIs (aPR: 3.50 (95% CI: 1.09 to 11.21)) but negatively associated with urethral STIs. Conclusion: MSM/TGW, especially those living with HIV, are at high risk of STIs in Rwanda with the vast majority being asymptomatic. These data suggest the potential utility of active STI surveillance strategies using highly sensitive laboratory methods among those at high risk given the anatomical distribution and limited symptomatology of STIs observed among Rwandan MSM/TGW.